Biliary strictures and recurrence after liver transplantation for primary sclerosing cholangitis: A retrospective multicenter analysis. Issue 1 (January 2016) - Hildebrand, Tatiana; Pannicke, Nadine; Dechene, Alexander; Gotthardt, Daniel N.; Kirchner, Gabriele; Reiter, Florian P.; Sterneck, Martina; Herzer, Kerstin; Lenzen, Henrike; Rupp, Christian; Barg‐Hock, Hannelore; de Leuw, Philipp; et al.
Abstract : Liver transplantation (LT) is the only definitive treatment for patients with end‐stage liver disease due to primary sclerosing cholangitis (PSC), but a high rate of biliary strictures (BSs) and of recurrent primary sclerosing cholangitis (recPSC) has been reported. In this multicenter study, we analyzed a large patient cohort with a long follow‐up in order to evaluate the incidence of BS and recPSC, to assess the impact on survival after LT, and to identify risk factors. We collected clinical, surgical, and laboratory data and records on inflammatory bowel disease (IBD), immunosuppression, recipient and graft outcome, and biliary complications (based on cholangiography and histology) of all patients who underwent LT for PSC in 10 German transplant centers between January 1990 and December 2006; 335 patients (68.4% men; mean age, 38.9 years; 73.5% with IBD) underwent transplantation 8.8 years after PSC diagnosis with follow‐up for 98.8 months. The 1‐, 5‐, and 10‐year recipient and graft survival was 90.7%, 84.8%, 79.4% and 79.1%, 69.0%, 62.4%, respectively. BS was diagnosed in 36.1% after a mean time of 3.9 years, and recPSC was diagnosed in 20.3% after 4.6 years. Both entities had a significant impact on longterm graft and recipient survival. Independent risk factors for BS were donor age, ulcerative colitis, chronic ductopenic rejection, bilirubin, and international normalized ratio (INR) at LT. Independent risk factors for recPSC were donor age, IBD, and INR at LT. These variables were able to categorize patients into risk groups for BS and recPSC. In conclusion, BS and recPSC affect longterm graft and patient survival after LT for PSC. Donor age, IBD, and INR at LT are independent risk factors for BS and recPSC and allow for risk estimation depending on the recipient‐donor constellation. Liver Transpl 22:42‐52, 2016 . © 2015 AASLD.